2021
DOI: 10.2196/24152
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Extended Reality in Ophthalmology: Systematic Review

Abstract: Background: Virtual reality, augmented reality, and mixed reality make use of a variety of different software and hardware, but they share three main characteristics: immersion, presence, and interaction. The umbrella term for technologies with these characteristics is extended reality. The ability of extended reality to create environments that are otherwise impossible in the real world has practical implications in the medical discipline. In ophthalmology, virtual reality simulators have become increasingly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 136 publications
0
64
0
Order By: Relevance
“…For example, EYESI, a surgical simulator. A systematic review reported that 38 publications had held evaluation experiments on it (70). As a result, the development of AR in medical education is more mature than in other fields in ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, EYESI, a surgical simulator. A systematic review reported that 38 publications had held evaluation experiments on it (70). As a result, the development of AR in medical education is more mature than in other fields in ophthalmology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared to VR, the vision of AR simulation is more realistic and vivid because it is based on the natural environment. However, the evaluation of AR simulators is still lacking (70). In public education, obstacles still exist in evaluating several disease simulations, such as simulating the vision of color blindness.…”
Section: Discussionmentioning
confidence: 99%
“…79 Heads-up surgery is another application of extended reality technology using a 3D camera to capture images from a stereomicroscope for presentation on a 3D display for greater surgeon maneuverability and comfort. 69 At present, studies have demonstrated noninferiority of heads-up surgery in comparison with conventional microscope surgery in postoperative outcomes and complications. 80,81 In particular, researchers compared the use of 3D heads-up microscope with traditional ophthalmic microscope for pars-plana vitrectomy in 50 eyes, and found heads-up surgery demonstrated greater ergonomics and comfort for the surgeon, without compromising on safety, with no major complications and similar operating times.…”
Section: Therapeuticsmentioning
confidence: 99%
“…The most common surgical procedure simulated was cataract surgery followed by vitreoretinal procedures, 62,65 along with other glaucoma and corneal surgeries 66 . Several studies evaluated the use of extended reality as a tool for education in ophthalmoscopy 67 and optometry training, 68 and found that simulators demonstrated efficacy and validity in improving surgical and ophthalmoscopy skills 69 …”
Section: Potential Uses In Ophthalmologymentioning
confidence: 99%
See 1 more Smart Citation